PENERAPAN MODEL PEMBELAJARAN PROBING-PROMPTING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI WAWASAN KEBANGSAAN (Penelitian Tindakan Kelas VIII-K SMPN 1 Cimahi) - Annisa Amalia Prasetya, - (2022)
This research is motivated by various problems in learning activities in Class VIII-K SMPN 1 Cimahi. Researchers carry out pre-learning observation and found that there are problems in Class VIII-K, namely the ability to think critically that is still low among students in PPKn learning, especially when studying material that contains National insight. Therefore, the holding of this study aims to improve the critical thinking skills of students using the probing-prompting learning model as an effort to make students active in learning activities in the classroom through in-depth question and answer activities in studying PPKn, especially on material that contains National insight. This study uses a class action research method consisting of three cycles where from each cycle can be seen the changes that occur. Data collection techniques used in the form of interviews, observation, documentation and tests. The results obtained from this study are: (1) planning before applying the probing-prompting learning model is prepared as well as possible by preparing lesson plans, research instruments, Learning media and LKPD; (2) Learning is carried out through 3 cycles and there is an increase in the activities of teachers and students; (3) critical thinking skills of students have increased both individually and in groups; (4) Constraints in the application of probing-prompting learning model experienced by teachers and students teruma in question and answer activities but it can be pursued through cooperation between teachers and students.